Development of a Negative Stiffness Bistable Damper for Structural Vibration Control - Liming Fan; Chen Huang; Linsheng Huo (Shock and Vibration, 2022)
Linear dampers have been widely applied for suppressing the dynamic responses of structures to mitigate their damage. However, the primary disadvantage of the classical linear damper is that it is vulnerable to detuning, which has become an issue of great importance recently due to a great reduction in vibration control performance. To overcome the shortcoming, this study develops a negative stiffness bistable damper (NSBD) composed of a simple assembly consisting of a bistable buckling beam with a mass. Energy is dissipated through the transformation between the bistable states. The constitutive equation of the NSBD is derived to analyze the effects of the stiffness ratio, the arch-span ratio, and the damping ratio on its restoring capabilities. The vibration reduction effect of the NSBD is experimentally evaluated under different sinusoidal and seismic excitations in shaking table tests. The obtained results reveal that the NSBD can effectively restrain structural displacements.